Changes in population biology of three coral reef fishes in the South China Sea between 1998–1999 and 2016–2019 - Zhang, Jun; Cai, Yancong; Li, Jiajun; Zhang, Kui; Gong, Yuyan; Chen, Sen; Chen, Zuozhi (Frontiers in Conservation Science, 2023)
The decline of coral reefs and their fish has attracted worldwide attention. The South China Sea is the important center of coral reefs. Reef-fish is a crucial component in coral reef ecosystem. However, studies on the long-term variation in the biololgy of coral reef fish in the South China Sea are very lacking. To enhance our understanding of variation in reef fish biology in the South China Sea, we investigated long-term changes in some biological indicators of three dominant coral reef fishes (Lutjanus kasmira, Gnathodentex aureolineatus, and Cephalopholis urodeta) at the Yongshu Reef of the South China Sea between 1998–1999 and 2016–2019, and examined the effects of fishing and sea surface temperature on their biology. Compared with 1998–1999, average body length, average body mass, large fish indicator, feeding level and relative fatness of Lutjanus kasmira and Gnathodentex aureolineatus decreased in 2016–2019, but Cephalopholis urodeta did not. The relative fatness was positively correlated with the feeding level, which indicated that the decline of feeding level decreased the relative fatness. Fishing had the most important negative impact on biological changes. In the past two decades, Lutjanus kasmira had the most obvious decline in size and relative fatness, followed by Gnathodentex aureolineatus, but Cephalopholis urodeta had almost no decline. We hypothesized that different coral reef fishes have different abilities to maintain population stability under external pressures, and the differences in vulnerability of three fish species were the main reasons for their different responses to external pressures. To promote the conservation of coral reef fish, we recommend taking rigorous management to protect habitat.